(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
The article analyzes the version provided by the soldier chronicler of the 16th century, Pedro Cieza de León in his Crhonicle of peru about the war between incas and chancas. This famous and particular battle is recounted by different Andean chroniclers. Since, after the inca victory began the Tawantinsuyu, or Inca Empire. Specifically, I focus to study the per- spective provided by Cieza and particular and significant elements that provided this story about the episode of that confrontation.